Pengaruh Kualitas Produk Dan Citra Merek Terhadap Minat Beli Ulang Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Pada Dirgantara Cake Di Lampung Timur - Utari Alda; Kuncoro Budi Riyanto; Andiana Rosid (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the direct effect of product quality and brand image onrepurchase intention through customer satisfaction as an intervening variable. This researchis a quantitative research by measuring product quality variables. Brand image, repurchaseintention, and satisfaction using a closed questionnaire. The questionnaire scoring scale foreach variable is 1-5 so that theoretically the range of scores obtained by respondents isbetween 20-100. Data collection was carried out by distributing questionnaires to a sampleof 50 respondents. Data analysis in this study used path analysis (Path) with the help of theSPSS Version 25.0 application. The results showed that there was a direct influence betweenproduct quality and customer satisfaction at Dirgantara Cake in East Lampung. There is adirect influence of brand image on customer satisfaction at Dirgantara Cake in EastLampung. There is a direct influence on product quality on the repurchase intention ofDirgantara Cake customers in East Lampung. There is a direct influence of brand image onthe repurchase intention of Dirgantara Cake customers in East Lampung. There is a directinfluence between customer satisfaction and repurchase intention of Dirgantara Cakecustomers In East Lampung